PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENUMBUHKAN SIKAP PEDULI LINGKUNGAN DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 2 PANCALANG KABUPATEN KUNINGAN - Atul, Sholihatul Maula; Umamatul Khaeriyah; Mahfud; Yoyoh Badriyah (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2023)
Various natural disasters often occur nowadays, as time goes by environmental damage becomes more widespread, this problem certainly cannot be underestimated, because it will have a negative impact and endanger human survival. The cause of this problem is certainly not far from the actions of humans, who always overexploit nature and never protect nature. A similar problem occurred at State Junior High School 2 Pancalang, Kuningan Regency. Through the interview and observation process, it was discovered that students showed an attitude of not caring about the school environment, such as throwing rubbish carelessly, not doing class picket work, and not keeping the school environment clean. This is the background to which this research was conducted. This research uses a qualitative approach with data collection techniques through interviews, observation and documentation. This research provides a conclusion that Islamic Religious Education teachers have a significant role in fostering an attitude of caring for the environment at SMP Negeri 2 Pancalang, Kuningan Regency.